2001
DOI: 10.1128/aem.67.4.1893-1901.2001
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure of Denitrifiers, Bacteria , and Archaea along Redox Gradients in Pacific Northwest Marine Sediments by Terminal Restriction Fragment Length Polymorphism Analysis of Amplified Nitrite Reductase ( nirS ) and 16S rRNA Genes

Abstract: Steep vertical gradients of oxidants (O

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
171
5
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(186 citation statements)
references
References 35 publications
2
171
5
8
Order By: Relevance
“…NosZ genotypes are known to exhibit high habitat specificity (Rö sch et al, 2002;Rich et al, 2003;Rich and Myrold, 2004;Stres et al, 2004), with few genotypes shared between sites with different C:N, pH, dominant vegetation and N availability (Rich et al, 2003). Experiments using other denitrification gene markers confirm that denitrifier gene communities tend to be unique to the environment from which they are sampled, with few genotypes shared between locations (Braker et al, 2000(Braker et al, , 2001. Large variations in nosZ TRF distribution at distances of centimeters, meters and especially kilometers has also been found in marine studies, which is consistent with observations that terrestrial denitrifier genotypes are strongly structured by site (Scala and Kerkhof, 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NosZ genotypes are known to exhibit high habitat specificity (Rö sch et al, 2002;Rich et al, 2003;Rich and Myrold, 2004;Stres et al, 2004), with few genotypes shared between sites with different C:N, pH, dominant vegetation and N availability (Rich et al, 2003). Experiments using other denitrification gene markers confirm that denitrifier gene communities tend to be unique to the environment from which they are sampled, with few genotypes shared between locations (Braker et al, 2000(Braker et al, , 2001. Large variations in nosZ TRF distribution at distances of centimeters, meters and especially kilometers has also been found in marine studies, which is consistent with observations that terrestrial denitrifier genotypes are strongly structured by site (Scala and Kerkhof, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Denitrification is generally thought to be more strongly associated with anaerobic conditions. However, Braker et al (2001) used an alternative denitrification marker (nirS) to investigate changes in community structure in ocean sediment cores based upon the transition to an anaerobic environment and as depth increased only a slight decrease in denitrifier diversity was detected in deeper samples even though a strong redox gradient was present. Enzyme analysis and gene probing of forest soils have also shown that denitrifier abundance decreases with depth despite lower levels of oxygen in deep samples (À25 cm) that should favor anaerobes (Mergel et al, 2001;Rö sch et al, 2002).…”
Section: Long-term Experimental Warming and Nitrogen-cycling Communitmentioning
confidence: 99%
“…Aquat Microb Ecol 51: [129][130][131][132][133][134][135][136][137][138][139][140] 2008 ment (Nogales et al 2002), marine sediments (Braker et al 2000(Braker et al , 2001, aquifers (Santoro et al 2006), seawater (Jayakumar et al 2004, Castro-Gonzalez et al 2005) and the oxygen minimum zone of the Black Sea (Oakley et al 2007). In marine environments a shift in the community structure of nirS denitrifying bacteria occurs along the physical-chemical gradient in the stratified water column (Castro-Gonzalez et al 2005, Oakley et al 2007.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Using the nitrite reductase genes as functional markers, the community composition of denitrifying bacteria has been studied in different habitats, including soil (Avrahami et al 2002, Prieme et al 2002, Rösch et al 2002, groundwater (Yan et al 2003), estuarine sedi-ment (Nogales et al 2002), marine sediments (Braker et al 2000(Braker et al , 2001, aquifers (Santoro et al 2006), seawater (Jayakumar et al 2004, Castro-Gonzalez et al 2005) and the oxygen minimum zone of the Black Sea (Oakley et al 2007). In marine environments a shift in the community structure of nirS denitrifying bacteria occurs along the physical-chemical gradient in the stratified water column (Castro-Gonzalez et al 2005, Oakley et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The amplicons are digested with one or more restriction enzymes (which recognize a particular nucleotide sequence, hence restriction site varies with the sequence of the amplicon) and electrophoretic separation. This technique has been used in study of entire marine bacterial assemblages using 16S rRNA as a target, (Moeseneder et al, 2001;Morris et al, 2005), as well as functional groups such as denitrifying bacteria (Braker et al, 2001), methanogens (Leuders and Friedrich, 2003) and nitrogen-fixers . The advantages of this technique include the ability to predict restriction site, and hence restriction fragment length, from public databases and in silico restriction digests.…”
Section: "Fingerprinting" Methods For Diversity Studiesmentioning
confidence: 99%